BBC English with an Accent: “African” and “Asian” Accents and the Translation of Culture in British Broadcasting - Steffensen, Kenn (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
Foreign accents acted by Anglophone actors are a ubiquitous but politically and theoretically problematic feature of many audiovisual productions in the English-speaking world. This paper investigates the use of Tswana and Japanese accents in two BBC productions as acts of audiovisual translation (AVT) which are illustrative of a more general problematic of Western representations of non-Western languages and cultures. It argues that the phonological features of speech, which are classified as accents, divide the community of native speakers into different social groups and that they create and maintain boundaries between native and non-native speakers. Language discrimination is recognised by the BBC as a problem in relation to its domestic audience and the Corporation actively attempts to become more inclusive and representative of British society by broadcasting non-standard accents. On the other hand, when representing foreign, and especially post-colonial and non-Western languages and cultures, accent is used to define the boundary between the native English-speaking community and its outside. Accents are used to represent and translate the outside in stereotyping ways that tend towards racialisation and towards actors using generic “Southern African” and “East Asian” accents that bear little resemblance to the actual phonological profile of native speakers of Tswana and Japanese.